Preoperative Ustekinumab Treatment Is Not Associated With Increased Postoperative Complications in Crohn's Disease: A Canadian Multi-Centre Observational Cohort Study. Issue 3 (10th May 2018) - Shim, Hang Hock; Ma, Christopher; Kotze, Paulo G; Seow, Cynthia H; Al-Farhan, Heba; Al-Darmaki, Ahmed K; Pang, Jack X Q; Fedorak, Richard N; Devlin, Shane M; Dieleman, Levinus A; Kaplan, Gilaad G; Novak, Kerri L; et al.
Abstract: Background: Ustekinumab (UST), an anti-IL12/23 inhibitor is indicated for moderate-to-severe Crohn's disease (CD). However, it is unclear if patients treated with UST are at increased risk for postoperative complications. Aim: To evaluate the postoperative safety outcomes in UST-treated CD patients. Methods: A multicentre cohort study of UST-treated CD patients at two tertiary care centres (University of Calgary, University of Alberta, Canada) undergoing abdominal surgery between 2009 and 2016 was performed. Postoperative outcomes were compared against a control cohort of anti-TNF-treated patients over the same time-period. The primary outcome was occurrence of postoperative complications up to six months postoperatively, stratified by timing (early <30 days vs. late complications ≥30 days). Results: Twenty UST-treated patients and 40 anti-TNF-treated patients were included with a median preoperative treatment exposure of 6.5 months and 18 months, respectively (p=0.01). Bowel obstruction was the most common surgical indication in both cohorts. UST-treated patients were more likely to require an ostomy (70.0% vs. 12.5%, p<0.001) and be on combination therapy with either systemic corticosteroids or concurrent immunomodulators (azathioprine or methotrexate) (25.0% vs. 2.5%, p=0.01). Despite the increased concomitant use of immunosuppression in the UST-treated cohort, there were no significant differences in early or late postoperative wound infections (1/20 in UST-cohort, 2/40 in anti-TNF cohort, p=1.00), anastomotic leak (0/20 in UST-cohort, 3/40 in anti-TNF cohort, p=0.54), or postoperative ileus/obstruction (3/20 in UST-cohort, 4/40 in anti-TNF cohort, p=0.67). Conclusions: CD patients receiving preoperative UST did not experience an increase in postoperative complications, despite increased use of concurrent immunosuppression.